2010
DOI: 10.1080/00071668.2010.506907
|View full text |Cite
|
Sign up to set email alerts
|

The effect of breed and feed-type on the sensory profile of breast meat in male broilers reared in an organic free-range system

Abstract: To cite this Article Horsted, K. , Allesen-Holm, B. H. and Hermansen, J. E.(2010) 'The effect of breed and feed-type on the sensory profile of breast meat in male broilers reared in an organic free-range system', British Poultry Science, 51: 4, 515 -524 To link to this Article: DOI: 10.1080/00071668.2010.506907 URL: http://dx.doi.org/10.1080/00071668.2010.506907Full terms and conditions of use: http://www.informaworld.com/terms-and-conditions-of-access.pdf This article may be used for research, teaching and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
(35 reference statements)
0
12
0
3
Order By: Relevance
“…Other studies have shown that poultry meat characteristics are influenced by factors such as age,15, 27 feed28 and genotype, with the latter covering e.g. growth rate, body composition and locomotor activity 6, 15, 29–32. In the present study especially the texture attributes were significantly influenced as a consequence of the very different production characteristics of the standard and niche products.…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…Other studies have shown that poultry meat characteristics are influenced by factors such as age,15, 27 feed28 and genotype, with the latter covering e.g. growth rate, body composition and locomotor activity 6, 15, 29–32. In the present study especially the texture attributes were significantly influenced as a consequence of the very different production characteristics of the standard and niche products.…”
Section: Discussionmentioning
confidence: 41%
“…However, the fast‐growing broilers in that study were slaughtered at 63 days of age, whereas in our study the fast‐growing broilers (Standards A and B) were slaughtered at 38 days of age. Other studies have shown that poultry meat characteristics are influenced by factors such as age,15, 27 feed28 and genotype, with the latter covering e.g. growth rate, body composition and locomotor activity 6, 15, 29–32.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many consumers claim that products from ecological rearing are characterized by a higher nutritive quality and better taste [Midmore et al, 2005; Andree et al, 2010; Horsted et al, 2010]. It was confi rmed in a research by Fanatico et al [2006], who was explaining higher sensory values of meat of chickens reared with the access to free range by a decrease of stress factor resulting from high birds density per area unit.…”
Section: Introductionmentioning
confidence: 63%
“…It was confi rmed in a research by Fanatico et al [2006], who was explaining higher sensory values of meat of chickens reared with the access to free range by a decrease of stress factor resulting from high birds density per area unit. Other authors [Horsted et al, 2010] emphasize the significance of selecting appropriate birds to be suitable for alternative rearing systems. In the systems of less intensive production, the slow-growing birds prove well since their lower growth rate and lower body weight are factors facilitating better health status and lesser mortality [Fanatico et al, 2008;Mikulski et al, 2011].…”
Section: Introductionmentioning
confidence: 99%